Environmental Sustainability Analysis: Agricultural Carrying Capacity in Purbalingga Regency, Central Java - Yahya Ayyash Mudhopir; Muhammad Fadhlullah; Restu Ashaffat Fadilah (Prodi Ilmu Lingkungan Fakultas Sains dan Teknologi, 2026)
The agricultural sector has a significant impact on the economy and the livelihood of the people in Purbalingga, Central Java, where around 26.5% of total GRDP income in 2025 is expected to come from this sector. This substantial income is accompanied by a growth in the number of business fields by 8.23% in the same year. Despite continuous growth and development, the agricultural sector, particularly rice fields, faces critical issues, such as the high rate of agricultural land conversion. Data shows a decrease in rice field area from 17,471.85 hectares in 2009 to 16,309.62 hectares in 2022, with a similar trend occurring in garden land. This research aims to evaluate environmental sustainability through the calculation of the agricultural area's carrying capacity amidst the high trend of land conversion. The research results are expected to provide strategic recommendations that can be taken to maintain the advantages of this sector while weighing the risks that may arise if land conversion is allowed to continue.